Developing Learners’ Top-Down Processing Skills in Listening - Bekaryan, Lilit (Armenian Folia Anglistika, 2016)
Listening is the first receptive skill that we develop as human beings, and it helps us improve other skills and gain confidence as language learners. In the English language classroom, learners find listening tasks particularly frustrating and challenging for a range of reasons. The present research addresses ways of developing learners’ top-down processing skills, such as making predictions about the target text, guessing the context and using contextual clues to infer meaning.
Keywords: receptive skills; listening comprehension; top-down processing; listener-oriented strategies; listening tasks